2015
DOI: 10.1177/0284185115595667
|View full text |Cite
|
Sign up to set email alerts
|

Low dose CT of the lumbar spine compared with radiography: a study on image quality with implications for clinical practice

Abstract: Low dose lumbar spine CT at about 1 mSv has superior image quality to lumbar spine radiography with more anatomical and diagnostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…However, this direct comparison has already been performed by Alshamari, demonstrating the diagnostic superiority of CT. Furthermore, our study reported similar dose levels to plain radiographs, as previously described [ 1 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, this direct comparison has already been performed by Alshamari, demonstrating the diagnostic superiority of CT. Furthermore, our study reported similar dose levels to plain radiographs, as previously described [ 1 , 18 ].…”
Section: Discussionsupporting
confidence: 87%
“…Low dose CT (<1 mSv) of the spine has already shown superior image quality in terms of anatomical and diagnostic information [19]. CT allows for much more detailed evaluation of paravertebral ossifications and degenerative changes, which supports the conclusion that modifications of the Resnick criteria are necessary when applied to CT directly.…”
Section: Discussionmentioning
confidence: 74%
“…In the current study the CT scan settings were selected to give a DLP which would result in a suitable low effective dose, with the only requirement being that the dataset could be used for 3D reconstructions with the Ortoma software without noticeable artifacts. The settings of tube current and tube voltage are similar to those of the scanning protocol for lumbar spine CT with equivalent dose to radiography (9,21). In that project, careful subjective and objective image quality assessment were used to select the scan settings which gave the best image quality (21).…”
Section: Discussionmentioning
confidence: 99%
“…Due to advances in technology, low-dose CT applications are now available for many body parts, including the musculoskeletal system. For example, the lumbar spine can be imaged using CT with better image detail than radiography at the same dose of about 1 mSv (9), low-dose CT has been shown to be useful for pre- and postoperative imaging in scoliosis (10,11), in cervical spine trauma (12), and in staging of multiple myeloma (13). Previous studies have shown the applicability of low-dose CT in THA (7,14).…”
Section: Introductionmentioning
confidence: 99%